FTIR studies of PEMA/PVdF-HFP blend polymer electrolyte system incorporated with LiCF3SO3 salt - Sim, L.N.; Majid, Siti Rohana; Arof, Abdul Kariem (Elsevier, 2012)
Poly(ethyl methacrylate), PEMA and poly(vinylidenefluoride-co-hexafluoropropylene). PVdF-HFP have been chosen as hosts for the development of a polymer blend electrolyte system. Lithium trifluoromethanesulfonate (triflate), LiCF3SO3 is the lithium ion, Li+ provider. The ratio of PEMA:PVdF-HFP in the blend is fixed at 70:30 in order to obtain transparent films with good mechanical stability. The polymers and LiCF3SO3 salt have been refluxed for 2 h at temperatures between 55 and 65 degrees C. The concentration of LiCF3SO3 salt has been varied from 0 to 40 wt.%. Fourier transform infrared (FTIR) spectroscopy has shown that blending between PEMA and PVdF-HFP has occurred from the changes in the CH2 scissoring[delta(CH2)], asymmetrical O-C2H5 bending [gamma(OC2H5)], CH2 twisting [ tau(CH2)]. C-O stretching of -COO-group [upsilon(CO)], asymmetrical C-O-C stretching [upsilon(a)(COC)] and C-O stretching of -OC2H5 [upsilon(C-O)] from PEMA as well as the symmetrical CF2 stretching [upsilon(5)(CF2)], alpha-phase and the amorphous region of PVdF-HFP. Complexation occurs via the coordination of Li+ ions with the oxygen atom in the carbonyl (C=O) and ester (-COC-) groups of PEMA as well as with the fluorine atom in -CF2 and -CF3 groups in PVdF-HFP. Curve fitting of spectral bands in the symmetrical upsilon(5)(SO3) stretching region in the polymer blend-salt complexes has shown that free ions (1031-1032 cm(-1)) and ion pairs (1040-1042 cm(-1)) are present in samples incorporated with 10 wt.% LiCF3SO3 and above, while ion aggregates at 1049 cm(-1) are formed when 40 wt.% LiCF3SO3 is added into the polymer blend. The increase in the ionic conductivity at high salt contents could be explained by the greater amount of free ions as compared to ion pairs and ion aggregates. (C) 2011 Elsevier B.V. All rights reserved.